1997
DOI: 10.1074/jbc.272.40.24858
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Amino Terminus in the Kinetics and Assembly of α-Hemolysin of Staphylococcus aureus

Abstract: The nature of the involvement of an intact NH 2 terminus in the assembly of ␣-hemolysin of Staphylococcus aureus was reinvestigated. For the first time, a deletion of the first four amino acids at the NH 2 terminus of ␣-hemolysin yielded a novel mutant that undergoes all of the conformational changes to form a lytic pore. The experimental evidence shows unequivocally that the mutant toxin forms heat-and sodium dodecyl sulfatestable heptameric oligomers. The concentration required to achieve 50% lysis of red bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…1B). However, a later study suggested that truncated polypeptides have limited pore-forming activity (36). In the present work, we resolve this issue through an examination of the original truncation mutants and a new series in which up to 22 residues are deleted.…”
Section: Lytic (Stage 3mentioning
confidence: 98%
See 1 more Smart Citation
“…1B). However, a later study suggested that truncated polypeptides have limited pore-forming activity (36). In the present work, we resolve this issue through an examination of the original truncation mutants and a new series in which up to 22 residues are deleted.…”
Section: Lytic (Stage 3mentioning
confidence: 98%
“…The mutation has no effect on the activity of the full-length protein as discussed in the report (22). Nevertheless, a later study from another laboratory suggested that truncated polypeptides might have limited activity (36). Further, Panchal and coworkers (43) from our laboratory had discovered that a mutation at position 217 could partially reactivate the non-lytic mutant ␣HL-H35N.…”
Section: Construction Of ␣Hl Mutants To Analyze the Effect Of The Resmentioning
confidence: 99%
“…L1130). The complete 1 mM amino acid mixture minus methionine (2.5 l) or the complete 1 mM amino acid mixture minus cysteine (2.5 l) that was supplied in the kit was mixed with premix solution (10 l), [L- 35 S]methionine (1 l, ICN Biomedicals, Inc., Irvine, CA, 1175 Ci/mmol) or [ 35 S]cysteine (1 l, Amersham Biosciences, 1200 Ci/mmol), plasmid DNA (4 l, 400 ng/l), and T7-S30 extract (7.5 l) supplemented with rifampicin (20 g/ml final) to generate "hot" radiolabeled polypeptides (25 l) (24). Synthesis was carried out for 60 min at 30°C, and reactions were terminated with chloramphenicol (100 M final).…”
Section: Methodsmentioning
confidence: 99%
“…The complete amino acid mixture minus cysteine and the complete amino acid mixture minus methionine were mixed in equal volumes and replaced the individual amino acid mixture minus methionine (or cysteine) (2.5 l) to yield "warm" radiolabeled proteins. Unlabeled (cold) proteins were generated by replacing the [L- 35 (27) in MBSA (10 mM 3-[Nmorpholino]propane sulfonic acid (MOPS), 150 mM NaCl, pH 7.4, containing 1 mg/ml bovine serum albumin), in a final volume of 100…”
Section: Methodsmentioning
confidence: 99%
“…This leads us to the notion that, in membrane insertion, the central loop receives dual activation both from the NH 2 terminus in cis and from another central loop in trans. This model readily accommodates the second cluster of breakthrough mutations located within that loop, and it can also account for previous results obtained with an NH 2 -terminal deletion mutant (12). The latter protein exhibits impaired hemolytic activity, which it also imparts on wild type toxin within hybrid heptamers (Fig.…”
Section: Breakthrough Mutants Effect Pore Formation When Co-assembledmentioning
confidence: 54%